2017
DOI: 10.1093/pm/pnw292
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Lateral Rectus Muscle, the Supraorbital Nerve, and Binocular Coordination with Episodic Tension-Type Headaches Frequently Associated with Visual Effort

Abstract: The finding of a higher alteration of the sensitivity of the supraorbital nerve, the myofascial trigger points of the lateral rectus, binocular coordination, and the significant influence of visual effort in patients with tension-type headaches suggest a new clinical perspective for problems related to tension-type headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Patients with TTH are known to present with oculomotor disturbances, including a reduction in the speed of smooth pursuit and saccadic eye movements [ 13 ]. These oculomotor disturbances are related to dysfunction in the upper cervical structures [ 62 ], which may cause headaches owing to the convergence of cervical and trigeminal afferent fibers at the trigeminal–cervical complex [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with TTH are known to present with oculomotor disturbances, including a reduction in the speed of smooth pursuit and saccadic eye movements [ 13 ]. These oculomotor disturbances are related to dysfunction in the upper cervical structures [ 62 ], which may cause headaches owing to the convergence of cervical and trigeminal afferent fibers at the trigeminal–cervical complex [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the visual system is also involved in the development of PHD. In this regard, not only has a reduction in the speed of smooth pursuit and saccadic eye movements been observed, but also an affectation of binocular coordination during smooth pursuit movements in patients with TTH during continuous visual efforts maintained under inappropriate conditions [ 13 ]. Furthermore, vestibular dysfunction and non-specific balance disturbances have also been widely linked to headaches, despite the origin of their concomitance being unknown [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can cause characteristic signs such as pain, hypersensitivity to touch, disturbed motor activity, and autonomic symptoms [ 61 ]. Cachinero-Torre et al found a relation between hypersensitivity of the supraorbital nerve and the presence of an active trigger point in the lateral rectus of the eye in persons with tension-type headaches [ 62 ]. According to the International Headache Society, tension-type headaches (TTH) are the most common type of initial headaches in all age groups [ 63 ].…”
Section: Early Intervention and Nonpharmacological Therapy Of Myopmentioning
confidence: 99%
“…Vestibular, visual, and somatosensory systems play a major role in verticality perception [ 2 , 3 ]. Furthermore, it is frequently observed how disfunction in these three systems appear in conjunction with headache, taking an important part in headache development [ 15 , 16 , 17 ]. The possibility that patients with headaches could present some alterations in any of these three systems that may induce a misperception of VV has turned headache disorders into a study issue in relation to alteration of VV.…”
Section: Introductionmentioning
confidence: 99%